An improved method for quantitative ChIP studies of nuclear receptor function. (May 2019) - Hunter, Ann Louise; Narang, Natasha; Baxter, Matthew; Ray, David W; Poolman, Toryn M
Abstract : Chromatin immunoprecipitation (ChIP) is a valuable tool for the endocrine researcher, providing a means to measure the recruitment of hormone-activated nuclear receptors, for example. However, the technique can be challenging to perform and has multiple experimental steps, risking introduction of error at each. The data produced can be challenging to interpret; several different methods are commonly used for normalising data and thus comparing between conditions. Absolute, sensitive quantification of protein-bound DNA is important for correct interpretation of the data. In addition, such quantification can help the investigator in troubleshooting experiments. Here, we outline a ChIP strategy combining droplet digital PCR for accurate quantification with an internal spike-in control for normalisation. This combination strengthens the reliability of ChIP data and allows the operator to optimise their protocol with greater confidence.